Microbial Fuel Cell for Wastewater Treatment as Power Plant in Smart Grids: Utopia or Reality? - Tsekouras, George J.; Deligianni, Panagiota M.; Kanellos, Fotis D.; Kontargyri, Vassiliki T.; Kontaxis, Panagiotis A.; Manousakis, Nikolaos M.; Elias, Charalambos N. (Frontiers in Energy Research, 2022)
Microbial fuel cells (MFCs) have undergone great technological development in the last 20 years, but very little has been done to commercialize them. The simultaneous power production and wastewater treatment is a feature that greatly increases the interest in the use of MFCs. This kind of distributed power generation is renewable and friendly and can be easily integrated into a smart grid. However, there are some key issues with their commercialization: high construction costs, difficulty in developing high power structures, MFC lifespan and maintaining a high level of efficiency. The objective of this paper is to explore the possibilities of using microbial fuel cells in urban wastewater not only regarding the technical criteria of their application, but mainly from an economic point of view, in order to determine the conditions through which the viability of the investment is ensured, as well as to identify the possibilities of their integration in a smart grid. Initially, this article explores the implementation/configuration of a power plant with microbial fuel cells within an urban wastewater treatment plant. In addition, based on the corresponding physical quantities for urban wastewater treatment, the construction and operational costs are determined and the viability of the investment is examined based on classic economic criteria such as net present value, benefit cost ratio, internal rate of return and discounted payback period. Furthermore, sensitivity analysis is carried out, concerning both technical parameters, such as the percentage of organic matter removal, power density, sewage residence time, MFC efficiency etc., as well as economical parameters, such as reduction of construction costs due to change of materials, change of interest rate, lifetime. The advantages and disadvantages of their use in smart grids is also analyzed. The results show that the use of microbial fuel cells for power generation is not utopian as long as they are integrated into the structure of a central wastewater treatment plant.